Microbiological Characteristics of Intestinal Biocenosis of Ambulator Patients Having Behavioral Risk Factors for Chronic Non-Communicable Diseases - I. A. Krylova; V. I. Kupaev; A. V. Ljamin (Архивъ внутренней медицины)
The earliest correction of behavioral risk factors for chronic non-communicable diseases will reduce the rates of premature mortality of the population. Currently, the relationship between the altered spectrum of intestinal microflora in various indicators of suboptimal health status and body mass index is not sufficiently studied. When they are in a state of suboptimal health status, patients consider themselves healthy and do not go to the doctor for a long time, which makes it difficult to implement early preventive measures in this group of patients. Goal. To determine the qualitative and quantitative composition of the intestinal microflora before and 1 month after taking a metaprebiotic complex containing dietary fiber (inulin) and oligosaccharides (oligofructose) in outpatient patients who consider themselves healthy, have behavioral risk factors for chronic non-communicable diseases or chronic non-communicable diseases in remission, and/or do not consult a doctor within the last 3 months. Materials and methods. Outpatient patients were examined (114 people: 36 men, 78 women aged 18 to 72 years). A survey was conducted, including a detailed active collection of complaints (including using the international SHSQ-25 questionnaire) and anamnesis, as well as a thorough physical examination with an anthropometric study. Using the MALDI-ToF mass spectrometry method, the degree of microbiotic disorders, the structure of the intestinal microflora were determined with the identification of microorganisms isolated from feces before and after taking the course of the metaprebiotic complex with various indicators of suboptimal status and body mass index. Results. New data were obtained on the intestinal biocenosis of patients who consider themselves healthy at different levels of suboptimal status. When using a metaprebiotic complex containing inulin and oligofructose, an improvement in the composition of the intestinal microflora was found due to a decrease in the frequency of release of conditionally pathogenic enterobacteria and other gram-negative microorganisms (median degree of contamination: from 0.45 (0.3-0.98) to 0.3(0.21-0.7) at low suboptimal status and from 0.5(0.7-1.7) to 0.31 (0.2-1.3) at high) and increase the frequency of enterococcal excretion (median degree of contamination: from 5,58 (4,16-7,0) tо 6,3 (4,8-7,8) at low suboptimal status and from от 4,5 (2,8-6,3) tо 5,1 (3,8-6,4) at high). Conclusion. The importance of studying the microbiotic complex of the intestine in increasing the indicators of suboptimal health status and body mass index in patients who consider themselves healthy is proved, which will allow for the earliest detection and rational individual prevention of chronic non-communicable diseases.